Algorithm accumulation-Jump step problem __ Algorithm

Source: Internet
Author: User
algorithm accumulation-jump step problem topic One: A frog can jump up to 1 steps at a time, can also jump up to level 2. How many jumps are there in total for the frog to jump up the N-level steps? parsing: is to find the law of the algorithm, set F (n) to jump the N-Step jump method, starting from 1 to find the law:
F (1) = 1;
F (2) = 2;
F (3) = 3;
F (4) = 5;
...
F (n) = f (n-1) = f (n-2);
can be seen is the Fibonacci sequence, for this problem from the beginning of each number of n=3 is equal to the sum of the results of the first two. can be done recursively or iteratively, because recursion contains a lot of repetition, so it's better to use iterative efficiency. Recursive method
    public int Jump (int n) {
        if (n <= 0) {
            return-1;
        }
        Switch (n) {case
            1: Return
                1;
            Case 2: Return
                2;
            Default: Return
                Jump (n-1) + Jump (n-2);
        }
    
Iterative Methods
    public int Jump1 (int n) {
        if (n <= 2) {return
            n;
        }
        int fron = 1;
        int NEX = 2;
        int sum = 0;
        for (int i = 3; I <= n; i++) {
            sum = fron + NEX;
            Fron = NEX;
            NEX = sum;
        }
        return sum;
    }
topic Two: A frog can jump up to 1 steps at a time, can also jump up to level 2 ... It can also jump up n levels. How many jumps are there in total for the frog to jump up an n-level step? This problem is called crazy jump step, on the basis of common jump steps need to deepen some understanding There are several ways to understand this problem: First Type:
F (1) = 1;
F (2) = f (2-1) + f (2-2) = 1 + 1 = 2; The first jump step after the rest of the steps of the number of jumps + the first jump 2 order the remaining steps to jump the method
F (3) = f (3-1) + f (3-2) + f (3-3) = f (2) + f (1) +1 = 4  ;//meaning similar to 
  f (4) = f (4-1) + f (4-2) + f (4-3) + f (4-4)  = f (3 + F (2) + f (1) + 1 = 8;
...
F (n) = f (n-1) +f (n-2) +f (n-3) +...+f (n-n);
then we can find the law: F (n) = 2*f (n-1); The code is (you can also use an iterative method, of course):
if (n = = 1) {return
            1;
        }
        Return JUMP1 (n-1) * 2
The second understanding: Each step has two states, except the last step must jump, jump and do not jump two states, then the method is f (n) = 2^ (n-1); The code is:
    public int Jump2 (int n) {return
        (int) Math.pow (2, n-1);
    }
Read the comments to learn another way, on a line of code, as follows: personally think is the second method of another way of writing, a little read ...
    public int Jump3 (int n) {return
        1 <<--n;
    }

Contact Us

The content source of this page is from Internet, which doesn't represent Alibaba Cloud's opinion; products and services mentioned on that page don't have any relationship with Alibaba Cloud. If the content of the page makes you feel confusing, please write us an email, we will handle the problem within 5 days after receiving your email.

If you find any instances of plagiarism from the community, please send an email to: info-contact@alibabacloud.com and provide relevant evidence. A staff member will contact you within 5 working days.

A Free Trial That Lets You Build Big!

Start building with 50+ products and up to 12 months usage for Elastic Compute Service

  • Sales Support

    1 on 1 presale consultation

  • After-Sales Support

    24/7 Technical Support 6 Free Tickets per Quarter Faster Response

  • Alibaba Cloud offers highly flexible support services tailored to meet your exact needs.